2021
DOI: 10.1186/s13244-021-01059-6
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in non-bacterial osteomyelitis in children and adolescents: diagnosis, differential diagnosis and follow-up—an educational review based on a literature survey and own clinical experiences

Abstract: Background Chronic non-bacterial osteomyelitis (CNO) is an autoinflammatory bone disorder affecting children and adolescents. Previously classified as a rare disease, recent studies suggest a higher incidence of the disease. CNO may develop into the clinical presentation of chronic recurrent osteomyelitis (CRMO) with high relapse rate and multifocality. Main body Diagnosis of CNO/CRMO is often delayed, with implications for disease severity and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…8,13 Most recently, whole-body magnetic resonance imaging (WBMRI) has emerged as the imaging modality of choice, often obviating bone biopsy providing scanning of the whole skeleton within an acceptable examination time and revealing multiple bone lesions [14][15][16][17] many of them being asymptomatic. 5,18 During our clinical practice, we noticed some variations in WBMR imaging patterns of our patients with CNO, all of them being of Greek origin, compared with previous studies, such as paucity of spinal lesions except for the sacrum and involvement of the bones of ankles and feet in even higher frequency than previously described. In this retrospective study, we attempted to evaluate the imaging findings and patterns of CNO on WBMRI in a series of Greek pediatric patients.…”
Section: Introductionsupporting
confidence: 47%
See 2 more Smart Citations
“…8,13 Most recently, whole-body magnetic resonance imaging (WBMRI) has emerged as the imaging modality of choice, often obviating bone biopsy providing scanning of the whole skeleton within an acceptable examination time and revealing multiple bone lesions [14][15][16][17] many of them being asymptomatic. 5,18 During our clinical practice, we noticed some variations in WBMR imaging patterns of our patients with CNO, all of them being of Greek origin, compared with previous studies, such as paucity of spinal lesions except for the sacrum and involvement of the bones of ankles and feet in even higher frequency than previously described. In this retrospective study, we attempted to evaluate the imaging findings and patterns of CNO on WBMRI in a series of Greek pediatric patients.…”
Section: Introductionsupporting
confidence: 47%
“…[1][2][3] The term autoinflammatory bone disease includes a spectrum of spontaneous activation of the immune system, leading to non-specific inflammatory processes in bones. This disorder is gaining medical momentum in recent years [3][4][5] and is considered the clinical and pathophysiologic counterpart of SA-PHO syndrome in adults, 6 while associated with seronegative arthritides. [7][8][9] CNO can affect almost any bone type, most commonly tibial and femoral metaphyses, followed by pelvic bones, spine, and clavicle, 8,[10][11][12][13] and is characterized by spontaneous remissions and exacerbations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI is also inferior compared to CT in accurately evaluating some of the characteristic structural morphological changes of CNO such as sclerosis (particularly when subtle), hyperostosis, ligamentous calcifications, erosions and ankylosis in the ACW, which are key to establishing the diagnosis. 23 , 45-47 …”
Section: Discussionmentioning
confidence: 99%
“…Though this disorder is considered rare, its actual prevalence might be higher than reported. It is thought to be underdiagnosed due to false identification as one of the numerous differential diagnoses of CRMO [ 19 , 20 ]. Though the genetic background of CRMO has not yet been precisely elucidated [ 21 ], the results of recent genetic studies showed significant differences in gene expression between patients with CRMO and otherwise healthy study participants [ 22 ].…”
Section: Discussionmentioning
confidence: 99%